TINJAUAN YURIDIS TERHADAP PENGEMBALIAN KEWENANGAN ISTIMEWA MAJELIS PERMUSYAWARATAN RAKYAT MELALUI PERUBAHAN UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 - Wierdarini, Putu Ayu Anastasia (Jurnal Yuridis, 2018)
The amendment of the Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 positioned the Majelis Permusyawaratan Rakyat no longer as the highest state institution and the highest sovereign of the people. This has implications for the authority of the Majelis Permusyawaratan Rakyat to have a strategic position, namely to UUD 1945, to stipulate GBHN, to elect the president and vice president through amendment of its authority to be very limited and weak. This paper examines jurisdictionally how to restore the privileges possessed by the Majelis Permusyawaratan Rakyat through the amendment of the UUD 1945. A normative legal research method with statute approach and conceptual approach is used to analyze this problem.The results of the study indicate that the MPR's repatriation in the main and vital position in the Indonesian state administration system is very important, namely through amendments to the material content of the UUD 1945 which must be implemented on an ongoing basis.